Time Trends of Gastrointestinal Cancers Incidence and Mortality in Yangzhong From 1991 to 2015: An Updated Age-Period-Cohort Analysis - Shao, Yi; Hua, Zhaolai; Zhao, Lei; Shen, Yi; Guo, Xudong; Niu, Chen; Wei, Wenqiang; Liu, Fen (Frontiers in Oncology, 2018)
Background: Gastrointestinal (GI) cancers are the common cause of morbidity and mortality in China which seriously threaten people’s health and lives. The aim of this study was to describe the temporal trend in the epidemiology of GI cancers, with an emphasis on the effects of age, period and cohort in Yangzhong City, Jiangsu province, a high-risk area of GI cancers in China. Methods: Our study extracted cases of gastric cancer, esophageal cancer and colorectal cancer diagnosed from 1991 to 2015 from Yangzhong Cancer Registry. Age-standardized rates (ASRs) were calculated and joinpoint regression was used to compute the estimated annual percent changes. Age-period-cohort (APC) model was performed to investigate the independent effects of age, calendar period and birth cohort. Results: Between 1991 and 2015, 18,006 new cases and 10,262 deaths were registered with GI cancers in Yangzhong. The age-standardized incidence rates (ASIRs) of gastric cancer decreased in both sexes during the study period. And the incidence rates of esophageal cancer stabilized at first then continued to decline, the turning point was in 2005 for men and 2001 for women. Changes in the mortality rates of gastric cancer and esophageal cancer showed significant declined trends around 2000-2010 in both genders. The incidence rates of colorectal cancer increased steadily during the entire study period, and the increase was more pronounced in the mortality rates of men. The results of APC analysis suggest that general decreases in incidence and mortality of esophageal cancer and gastric cancer might be caused by the downward trend of the period and cohort effects, while the increases in colorectal cancer might be caused by the uptrend of the period effects. Conclusions: Different trends of incidence and mortality in GI cancers indicating heterogeneous etiologies exist between upper gastrointestinal cancers and colorectal cancer. Early detection and treatment programs are effective in reducing mortality of upper GI cancers and early childhood nutritional deficiencies may promote the development of GI cancers.